Improving professional IT doctorate completion rates - Burmeister, Oliver Kisalay (Australasian Journal of Information Systems, 2015)
Professional doctorates in Information Technology (IT) have been a relatively recent phenomenon, giving IT professionals career management choices not previously available to them. However, successful completion rates are the lowest of all disciplines. Completed doctorates rate in quality equivalent to PhDs, and retention has been identified as a major obstacle to completion. This qualitative study, involving 44 semi-structured interviews with students, supervisors and institutional support personnel, investigated the obstacles. Amongst the strategies discovered to improve completion rates were retention, student engagement with supervisors, feedback on progress, student engagement in the course, and student involvement in institutional communities of practice.